A systematic literature review of MTAP deletions in solid and hematologic Cancers - Mary C. Clouser; Mina Suh; Naimisha Movva; Janet S. Hildebrand; Susan T. Pastula; Martina Schoehl; Antreas Hindoyan; Akhila Balasubramanian; Jon P. Fryzek; Soo-Ryum Yang (Cancer Treatment and Research Communications)
Background: Methylthioadenosine phosphorylase (MTAP) deficiency is observed across multiple cancers and represents an emerging biomarker with therapeutic potential via synthetic lethality with PRMT5 inhibition. This systematic literature review summarizes the prevalence of MTAP deletions or loss of expression and prognostic impacts of MTAP deletions or loss in adult and pediatric patients with specific solid or hematologic cancers. Methods: Following PRISMA methodology, the literature on MTAP deletion or loss in multiple cancer types was reviewed. Prevalence, laboratory testing methods, patient characteristics, and clinical outcomes according to MTAP status were synthesized. Study quality was determined using standard tools. Results: Of the 352 identified studies, 37 reported on MTAP. The majority were retrospective cohorts (N=32; 86%). The most common laboratory test type was NGS, specifically FoundationOne (N=7, 24%). MTAP deletion (loss) prevalence varied across tumor types and were generally lowest in gastric cancer (4%–14%) and highest in glioblastoma (26%–60%). MTAP deletion was correlated with higher prevalence of KRAS. Variation by age, gender, and race/ethnicity were inconsistently reported. Survival outcomes were reported most often for GBM and NSCLC with some studies suggesting worse overall survival among patients with MTAP deletions, although the evidence was heterogeneous. Conclusion: This is the first systematic review to summarize the literature on MTAP deletions or loss of expression across several solid and hematologic cancers. MTAP deletions and/or loss of expression occur in many cancer types, presenting a promising target for pan-cancer therapy.